2019
DOI: 10.7441/joc.2019.02.05
|View full text |Cite
|
Sign up to set email alerts
|

An In-Depth Analysis of the Summary Innovation Index in the V4 Countries

Abstract: Innovative activity is an important source of competitiveness, economic growth, as well as the image of each country. There are several ways to measure and evaluate the innovation performance of a country. Our research was focused on the summary innovation index (SII), a tool used for analysing the innovative ability of European countries. The Innovation Union is an EU initiative which monitors progress achieved in research, development, and innovation, all indicators which are included in the SII. The aim of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 20 publications
0
20
0
Order By: Relevance
“…Following the annual reports of Global Competitiveness Index (G.C.I. ;Janoskova & Kral, 2019;Schwab, 2016Schwab, , 2017) of these countries, many differences can be found both in crucial macroeconomic indicators, i.e., the unemployment rate, inflation, GDP per capita and development of partial sectors of the economy, mainly the financial, business and institutional sectors. Determinants of economic growth of these countries are in details portrayed in the paper by Simionescu et al (2017).…”
Section: Research Resultsmentioning
confidence: 99%
“…Following the annual reports of Global Competitiveness Index (G.C.I. ;Janoskova & Kral, 2019;Schwab, 2016Schwab, , 2017) of these countries, many differences can be found both in crucial macroeconomic indicators, i.e., the unemployment rate, inflation, GDP per capita and development of partial sectors of the economy, mainly the financial, business and institutional sectors. Determinants of economic growth of these countries are in details portrayed in the paper by Simionescu et al (2017).…”
Section: Research Resultsmentioning
confidence: 99%
“…It is a commonly used indicator of innovation performance within empirical literature, e.g. [10], [11], which provides a comparative assessment of the innovation and research performance of the EU member states and selected third countries. The measurement framework distinguishes among four main types of activities and ten innovation dimensions, namely human resources, attractive research systems, innovation-friendly environment, finance and support, firm investments, innovators, linkages, intellectual assets, employment impacts and sales impacts, capturing in total 27 different indicators.…”
Section: університет економіки в братиславіmentioning
confidence: 99%
“…Another research findings from the period 2010-2016 used samples from the V4 countries are demonstrated in the paper with the theme ,,an in-depth analysis of the summary innovation index in the V4 countries. Slovakia belongs to the moderate innovators, the performance of Slovakia increased by 8% relative to that of the EU in 2010" [8]. The paradigms of European ,,integration process in the Visegrád group and its essence consider other authors as too simplistic to define only as consolidation of the efforts of Central European countries in order to return to Europe through Euro-Atlantic integration" [9].…”
Section: Theoretical Backgroundmentioning
confidence: 99%